Comparing Numerical Models of a Floating Oscillating Water Column (OWC) Wave Energy Converter (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Oscillating Water Column (OWC) Wave Energy Converters (WECs) are devices with a great potential to harvest energy from ocean waves. Accurate numerical models are crucial for the development of this technology, providing the means for power production, lifetime assessment, site selection, and design of mooring lines, PTO systems, and controllers among other aspects. The present work aims to compare four different numerical boundary element method (BEM) solvers and their results for the numerical modeling of a floating OWC. The solvers being compared are Ansys AQWA, WAMIT, Capytaine, and NEMOH. In addition to this, two different modeling approaches are compared in this paper. In the first approach, the main body of the WEC and the OWC are treated as two different bodies. In the second approach, the WEC and the OWC are considered a single body, and the position of the free surface of the oscillating water column is treated as an additional degree of freedom. Nonlinear hydrodynamics, considering viscous and nonlinear Froude-Krylov effects, are also implemented in a WEC-Sim model to study their influence in the numerical analysis of OWC systems.  The numerical model results are compared against existing experimental results for validation.